Social anxiety and suicidality in youth: a systematic review and meta-analysis - Leigh, E; Chiu, K; Ballard, E (Springer, 2022)
Suicide is a leading cause of death among young people every year. Identifying risk factors provides opportunities to intervene, and social anxiety may represent one such factor. This systematic review and meta-analysis aimed to review the evidence of associations between social anxiety and suicidality in youth (10–25 years). Embase, PsycInfo, and Medline were searched to identify relevant articles. Meta-analysis was conducted to examine the mean effect sizes of concurrent and prospective associations between social anxiety and three indices of suicidality in adolescents aged 10–25 years. Meta-analyses of 16 studies showed that social anxiety was associated cross-sectionally with suicide attempt (r = 0.10, 95% CI: 0.04, 0.15), suicidal ideation (r = 0.22, 95% CI: 0.02, 0.41), and suicide risk (r = 0.24, 95% CI: 0.05, 0.41), and prospectively at trend level with suicidal ideation (r = 0.62, 95% CI: -0.03, 0.90). An examination of the prospective associations with suicide attempt and risk was not possible due to a lack of studies. Several studies suggested that results could not be solely attributed to depressive symptoms. A high level of heterogeneity was observed in each meta-analysis. Moderation analysis was possible for gender and publication year only; neither was significant. Findings provide further evidence of a link between social anxiety and suicidal thoughts and behaviors in youth but are limited by the small number of studies of mixed quality. This review supports future research into social anxiety symptoms as potential risk factors and treatment targets for suicidal youth.